Vulcanized rubber-casting polyurethane composite material and preparation method thereof

By surface treatment of vulcanized rubber and using two-component adhesive, the problem that cannot be performed separately during the curing and forming of traditional rubber-polyurethane composite materials is solved, the bonding strength and dynamic fatigue resistance are improved, and the material is better cured.

CN119567661AInactive Publication Date: 2025-03-07JIHUA LAB

Patent Information

Application Number
CN202510125901.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional rubber-polyurethane composite materials cannot be separately carried out during the curing and forming process, which limits the processing and performance adjustment of the material. The existing structural adhesive layer has poor dynamic fatigue resistance, resulting in the composite material being easily degummed.

Method used

The vulcanized rubber is surface treated by using the surface treatment agent trichloroisocyanuric acid, and a two-component adhesive is used. Component A includes polymethylene polyisocyanate, and component B includes liquid nitrile rubber and nano-oxide filler to form an adhesive layer with good affinity and high adhesion strength, so as to achieve the successive curing of vulcanized rubber and cast polyurethane.

Benefits of technology

The bonding strength and dynamic fatigue resistance between vulcanized rubber and cast polyurethane are improved, and the structural regulation and better curing effect of the material are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119567661A_ABST
    Figure CN119567661A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of rubber-pouring type polyurethane composite products, and discloses a vulcanized rubber-pouring type polyurethane composite material and a preparation method thereof.The vulcanized rubber-pouring type polyurethane composite material is obtained by bonding and curing surface-treated vulcanized rubber and pouring raw materials through a two-component adhesive, wherein the pouring raw material is a mixture of a prepolymer of pouring type polyurethane and a chain extender; the surface-treated vulcanized rubber is obtained by coating the surface of vulcanized rubber with a surface treating agent; the two-component adhesive comprises polymethylene polyisocyanate and liquid nitrile rubber in a mass ratio of 100: (5-20). According to the invention, the vulcanized rubber is subjected to surface treatment by adopting a specific surface treating agent, and then the vulcanized rubber and the pouring polyurethane are bonded by adopting a double-component adhesive containing specific components, so that the vulcanized rubber and the pouring polyurethane can be cured in sequence and are tightly combined through the adhesive; and the vulcanized rubber and the casting polyurethane material can respectively realize different structural regulation and control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber-polyurethane composite products, and particularly relates to a vulcanized rubber-casting polyurethane composite material and a preparation method thereof. Background Art

[0002] In the preparation process of traditional rubber-polyurethane composite materials, the curing and molding of rubber and polyurethane need to be carried out at the same time, and they cannot be cured separately, which limits the convenience of material processing and performance adjustment. As the performance requirements of rubber-polyurethane composite materials in application scenarios become more and more stringent, the performance of rubber or polyurethane itself needs to be regulated separately. At this time, the curing and molding of rubber and polyurethane need to be carried out separately.

[0003] At present, structural adhesive can be used to bond rubber and cast polyurethane. Generally, the surface of the cast polyurethane after the curing process is polished, the structural adhesive is applied, and then it is pressed with the vulcanized rubber that has undergone the same treatment through mechanical tools. The structural adhesive is allowed to cure naturally to complete the bonding. The existing structural adhesive contains a curing agent with high reactivity. After the structural adhesive is cured, a hard adhesive layer is formed between the rubber and the cast polyurethane, and its dynamic fatigue tolerance is poor, which makes the rubber-cast polyurethane composite material easy to debond. Summary of the invention

[0004] The present invention aims to improve at least one technical problem in the background technology.

[0005] The present invention provides a vulcanized rubber-casting polyurethane composite material, wherein the vulcanized rubber-casting polyurethane composite material is obtained by bonding and curing a surface-treated vulcanized rubber and a casting raw material through a two-component adhesive, wherein the casting raw material is a mixture of a prepolymer of a casting polyurethane and a chain extender; The surface treated vulcanized rubber is obtained by coating the surface of the vulcanized rubber with a surface treating agent, wherein the surface treating agent includes trichloroisocyanuric acid; The two-component adhesive comprises component A and component B, wherein component A comprises polymethylene polyisocyanate, and component B comprises liquid nitrile rubber, wherein the liquid nitrile rubber is at least one of carboxyl-terminated liquid nitrile rubber and hydroxyl-terminated liquid nitrile rubber; and the mass ratio of the polymethylene polyisocyanate to the liquid nitrile rubber is 100:(5-20).

[0006] The present invention forms an adhesive layer with good affinity and high bonding strength between the vulcanized rubber and the cast polyurethane through the synergistic effect of trichloroisocyanuric acid, polymethylene polyisocyanate and carboxyl-terminated liquid nitrile rubber (or hydroxyl-terminated liquid nitrile rubber), thereby enabling the cast polyurethane to be bonded to the vulcanized rubber in a pouring and curing manner, thereby obtaining a vulcanized rubber-cast polyurethane composite material.

[0007] The two-component adhesive of the present invention contains polymethylene polyisocyanate and liquid nitrile rubber (the liquid nitrile rubber is at least one of a carboxyl-terminated liquid nitrile rubber and a hydroxyl-terminated liquid nitrile rubber), and the two components are combined by reaction of -NCO in the polymethylene polyisocyanate with -COOH in the liquid nitrile rubber (the liquid nitrile rubber is at least one of a carboxyl-terminated liquid nitrile rubber and a hydroxyl-terminated liquid nitrile rubber), and the two-component adhesive combination still contains -NCO and -COOH remaining from the reaction. On this basis, the present invention uses a surface treatment agent containing trichloroisocyanuric acid to perform surface treatment on the vulcanized rubber. Trichloroisocyanuric acid is an extremely strong oxidant and chlorinating agent. After the surface treatment, the surface of the vulcanized rubber undergoes the dual effects of oxidation and halogenation, and -OH will appear. The -OH can react and connect with the -NCO in the cast polyurethane prepolymer, and can also react and connect with the -NCO in the two-component adhesive combination. The sulfur and other vulcanizing agents remaining in the vulcanized rubber can form a small amount of crosslinking with the olefin chain segments in the liquid nitrile rubber (the liquid nitrile rubber is at least one of the carboxyl-terminated liquid nitrile rubber and the hydroxyl-terminated liquid nitrile rubber) contained in the two-component adhesive combination under heating conditions. Therefore, the surface treated vulcanized rubber of the present invention has good affinity with the two-component adhesive; there is a butadiene structural unit in the liquid nitrile rubber (the liquid nitrile rubber is at least one of the carboxyl-terminated liquid nitrile rubber and the hydroxyl-terminated liquid nitrile rubber), and its affinity with the vulcanized rubber is strong, which is conducive to the diffusion of the two-component adhesive conjugate on the vulcanized rubber side, so a stronger anchoring effect is formed after curing, and the bonding strength between the two-component adhesive conjugate and the vulcanized rubber is improved. In addition, the curing of the cast polyurethane is that the-NCO on its prepolymer is cured as a whole with the-OH or-NH2 on the chain extender. Meanwhile, on the basis of the reaction connection of-NCO on the prepolymer with-COOH in the two-component adhesive conjugate, the-NCO on the prepolymer can also be connected by the chain extender with-NCO reaction in the two-component adhesive conjugate, forming a certain amount of molecular chain entanglement, and then improving the bonding effect between the vulcanized rubber and the cast polyurethane.

[0008] Furthermore, the liquid nitrile rubber is a carboxyl-terminated liquid nitrile rubber, and the mass ratio of polymethylene polyisocyanate to the carboxyl-terminated liquid nitrile rubber is 100:15.

[0009] Furthermore, component A further comprises an organic solvent, and component B further comprises a nano-oxide filler.

[0010] Further, the organic solvent includes at least one of chlorobenzene, acetone and ethyl acetate.

[0011] Furthermore, the nano oxide filler includes at least one of nano zinc oxide and hydrophobic nano silicon dioxide. The use of nano oxide fillers can improve the anti-oxidation and moisture-proof properties of the adhesive, so that after the adhesive is cured into a film, it can resist the attenuation of the bonding effect caused by environmental changes; on a microscopic level, the nanoparticles of metal oxides and silicon oxides have good affinity with isocyanate compounds, which is beneficial to improving the thermal stability of the molecular chain, and on a macroscopic level, it will improve the adhesive's ability to maintain the bonding effect under high temperature conditions.

[0012] Furthermore, the mass ratio of the liquid nitrile rubber to the nano oxide filler is 100:1.5.

[0013] Furthermore, the chain extender includes at least one of diol, diamine and triamine, and the mass ratio of the chain extender to the prepolymer is (1-20):100.

[0014] A method for preparing the above-mentioned vulcanized rubber-cast polyurethane composite material comprises the following steps: The two-component adhesive is applied to the surface of the surface-treated vulcanized rubber, and placed under ventilation at room temperature for 1h-4h to completely volatilize the organic solvent, and then pre-cured at 100°C-130°C for 1h-3h to obtain the vulcanized rubber to be bonded; The casting process is followed by curing to obtain a vulcanized rubber-casting polyurethane composite material; the casting process includes the following steps: casting the casting raw material onto the surface of the vulcanized rubber to be bonded.

[0015] Furthermore, the two-component adhesive is obtained by mixing the component A and the component B, and the mixing method is mechanical stirring mixing or extrusion mixing. The extrusion mixing can be achieved by a two-component glue gun in combination with a mixing hose.

[0016] Furthermore, the pouring treatment includes the following process: adding a pouring material into a mold containing the vulcanized rubber to be bonded, so that the pouring material is poured onto the surface of the vulcanized rubber to be bonded.

[0017] Furthermore, the curing temperature is 90° C.-110° C., and the curing time is at least 18 hours.

[0018] The present invention benefits from the synergistic effect between trichloroisocyanuric acid, polymethylene polyisocyanate and carboxyl-terminated liquid nitrile rubber (or hydroxyl-terminated liquid nitrile rubber), and forms an adhesive layer with good affinity and high bonding strength between the vulcanized rubber and the cast polyurethane, and can achieve sequential curing of the vulcanized rubber and the cast polyurethane in the preparation of the vulcanized rubber-cast polyurethane composite material.

[0019] The beneficial effects of the present invention are as follows: the present invention uses a specific surface treatment agent to perform surface treatment on the vulcanized rubber, and then uses a two-component adhesive containing specific components to complete the bonding of the vulcanized rubber and the cast polyurethane. The vulcanized rubber and the cast polyurethane can be cured successively and tightly combined by the adhesive, and the vulcanized rubber and the cast polyurethane materials can respectively achieve different structural controls. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The infrared spectra of the adhesive layers of Examples 1-4 and Comparative Example 1 of the present invention are shown; Figure 2 The peeling test data of the embodiments of the present invention and the comparative examples are shown in FIG. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0022] The reagents / raw materials involved in the embodiments and comparative examples include: Vulcanized rubber: Dongyue Tire Retreading Products Factory, Dawang Town, Guangrao County, tire belt rubber Prepolymer for casting polyurethane: LANXESS M1056 Chain extender: Aladdin reagent, butanediol, AR Carboxyl-terminated liquid nitrile rubber: Lanzhou Petrochemical liquid nitrile rubber Hydrophobic nano-silica: Degussa Evonik hydrophobic white carbon black R202 Example 1 A vulcanized rubber-casting polyurethane composite material is obtained by bonding and curing a surface-treated vulcanized rubber and a casting raw material through a two-component adhesive, wherein the casting raw material is a mixture of a prepolymer and a chain extender of a casting polyurethane, and the mass ratio of the chain extender to the prepolymer is 9:100; the surface-treated vulcanized rubber is obtained by grinding the surface of the vulcanized rubber and coating a 3wt% trichloroisocyanuric acid-acetone solution; component A of the two-component adhesive is polymethylene polyphenyl isocyanate and a chlorobenzene solution, and the mass concentration of the polyphenyl isocyanate is 30wt%; component B of the two-component adhesive is a mixture of carboxyl-terminated liquid nitrile rubber and hydrophobic nano-silica, and the mass ratio of the carboxyl-terminated liquid nitrile rubber to the hydrophobic nano-silica is 100:1.5; and the mass ratio of the polymethylene polyisocyanate to the carboxyl-terminated liquid nitrile rubber is 100:5.

[0023] The preparation method is as follows: The two-component adhesive was coated on the surface of the surface-treated vulcanized rubber. After being placed under ventilation at room temperature for 1 hour, the surface-treated vulcanized rubber was placed in a mold and pre-cured at 110°C for 2 hours. Then, the casting raw material was added to the mold containing the vulcanized rubber to be bonded, and cured at 100°C for 18 hours to obtain a vulcanized rubber-casting polyurethane composite material.

[0024] Example 2 A vulcanized rubber-casting polyurethane composite material is obtained by bonding and curing a surface-treated vulcanized rubber and a casting raw material through a two-component adhesive, wherein the casting raw material is a mixture of a prepolymer of a casting polyurethane and a chain extender, and the mass ratio of the chain extender to the prepolymer is 9:100; the surface-treated vulcanized rubber is obtained by grinding the surface of the vulcanized rubber and coating a 3wt% trichloroisocyanuric acid-acetone solution; component A of the two-component adhesive is polymethylene polyphenyl isocyanate and a chlorobenzene solution, and the mass concentration of the polyphenyl isocyanate is 30wt%; component B of the two-component adhesive is a mixture of carboxyl-terminated liquid nitrile rubber and hydrophobic nano-silica, and the mass ratio of the carboxyl-terminated liquid nitrile rubber to the hydrophobic nano-silica is 100:1.5; and the mass ratio of the polymethylene polyisocyanate to the carboxyl-terminated liquid nitrile rubber is 100:10.

[0025] The preparation method is as follows: The two-component adhesive was coated on the surface of the surface-treated vulcanized rubber. After being placed under ventilation at room temperature for 1 hour, the surface-treated vulcanized rubber was placed in a mold and pre-cured at 110°C for 2 hours. Then, the casting raw material was added to the mold containing the vulcanized rubber to be bonded, and cured at 100°C for 18 hours to obtain a vulcanized rubber-casting polyurethane composite material.

[0026] Example 3 A vulcanized rubber-casting polyurethane composite material is obtained by bonding and curing a surface-treated vulcanized rubber and a casting raw material through a two-component adhesive, wherein the casting raw material is a mixture of a prepolymer and a chain extender of a casting polyurethane, and the mass ratio of the chain extender to the prepolymer is 9:100; the surface-treated vulcanized rubber is obtained by grinding the surface of the vulcanized rubber and coating a 3wt% trichloroisocyanuric acid-acetone solution; component A of the two-component adhesive is polymethylene polyphenyl isocyanate and a chlorobenzene solution, and the mass concentration of the polyphenyl isocyanate is 30wt%; component B of the two-component adhesive is a mixture of carboxyl-terminated liquid nitrile rubber and hydrophobic nano-silica, and the mass ratio of the carboxyl-terminated liquid nitrile rubber to the hydrophobic nano-silica is 100:1.5; and the mass ratio of the polymethylene polyisocyanate to the carboxyl-terminated liquid nitrile rubber is 100:15.

[0027] The preparation method is as follows: The two-component adhesive was coated on the surface of the surface-treated vulcanized rubber. After being placed under ventilation at room temperature for 1 hour, the surface-treated vulcanized rubber was placed in a mold and pre-cured at 110°C for 2 hours. Then, the casting raw material was added to the mold containing the vulcanized rubber to be bonded, and cured at 100°C for 18 hours to obtain a vulcanized rubber-casting polyurethane composite material.

[0028] Example 4 A vulcanized rubber-casting polyurethane composite material is obtained by bonding and curing a surface-treated vulcanized rubber and a casting raw material through a two-component adhesive, wherein the casting raw material is a mixture of a prepolymer of a casting polyurethane and a chain extender, and the mass ratio of the chain extender to the prepolymer is 9:100; the surface-treated vulcanized rubber is obtained by grinding the surface of the vulcanized rubber and coating a 3wt% trichloroisocyanuric acid-acetone solution; component A of the two-component adhesive is polymethylene polyphenyl isocyanate and a chlorobenzene solution, and the mass concentration of the polyphenyl isocyanate is 30wt%; component B of the two-component adhesive is a mixture of carboxyl-terminated liquid nitrile rubber and hydrophobic nano-silica, and the mass ratio of the carboxyl-terminated liquid nitrile rubber to the hydrophobic nano-silica is 100:1.5; and the mass ratio of the polymethylene polyisocyanate to the carboxyl-terminated liquid nitrile rubber is 100:20.

[0029] The preparation method is as follows: The two-component adhesive was coated on the surface of the surface-treated vulcanized rubber. After being placed under ventilation at room temperature for 1 hour, the surface-treated vulcanized rubber was placed in a mold and pre-cured at 110°C for 2 hours. Then, the casting raw material was added to the mold containing the vulcanized rubber to be bonded, and cured at 100°C for 18 hours to obtain a vulcanized rubber-casting polyurethane composite material.

[0030] Example 5 A vulcanized rubber-casting polyurethane composite material is obtained by bonding and curing a surface-treated vulcanized rubber and a casting raw material through a two-component adhesive, wherein the casting raw material is a mixture of a prepolymer and a chain extender of a casting polyurethane, and the mass ratio of the chain extender to the prepolymer is 9:100; the surface-treated vulcanized rubber is obtained by polishing the surface of the vulcanized rubber and coating a 3wt% trichloroisocyanuric acid-acetone solution; component A of the two-component adhesive is polymethylene polyphenyl isocyanate and a chlorobenzene solution, and the mass concentration of the polyphenyl isocyanate is 30wt%; component B of the two-component adhesive is a mixture of carboxyl-terminated liquid nitrile rubber and hydrophobic nano-silica, and the mass ratio of the carboxyl-terminated liquid nitrile rubber to the hydrophobic nano-silica is 100:1.5; and the mass ratio of the polymethylene polyisocyanate to the carboxyl-terminated liquid nitrile rubber is 100:30.

[0031] The preparation method is as follows: The two-component adhesive was coated on the surface of the surface-treated vulcanized rubber. After being placed under ventilation at room temperature for 1 hour, the surface-treated vulcanized rubber was placed in a mold and pre-cured at 110°C for 2 hours. Then, the casting raw material was added to the mold containing the vulcanized rubber to be bonded, and cured at 100°C for 18 hours to obtain a vulcanized rubber-casting polyurethane composite material.

[0032] Comparative Example 1 A vulcanized rubber-cast polyurethane composite material, which is different from Example 1 only in that component B of the two-component adhesive does not contain terminal carboxyl liquid nitrile rubber.

[0033] Comparative Example 2 A vulcanized rubber-cast polyurethane composite material, which is different from Example 1 only in that component A of the two-component adhesive does not contain polymethylene polyphenyl isocyanate.

[0034] Comparative Example 3 A vulcanized rubber-casting polyurethane composite material, which is different from Example 1 only in that the surface of the surface-treated vulcanized rubber is not coated with a two-component adhesive.

[0035] Comparative Example 4 A vulcanized rubber-cast polyurethane composite material, which is different from Example 1 only in that the surface of the surface-treated vulcanized rubber is only polished and is not coated with a 3wt% trichloroisocyanuric acid-acetone solution.

[0036] Comparative Example 5 A vulcanized rubber-cast polyurethane composite material, which is different from Example 1 only in that the surface of the surface-treated vulcanized rubber is only polished and is not coated with a 3wt% trichloroisocyanuric acid-acetone solution and a two-component adhesive.

[0037] The tests of the relevant properties of the products in the examples and comparative examples of the present application are as follows: (1) Determination of infrared spectrum Through infrared spectroscopy, the adhesive layer formed by the pre-curing reaction of the material is measured by infrared spectroscopy to analyze its chemical structure.

[0038] Figure 1 ] are infrared spectra of the adhesive layers of Examples 1-4 and Comparative Example 1. The raw materials for forming the adhesive layers in Examples 1-4 include trichloroisocyanuric acid, polymethylene polyphenyl isocyanate, and carboxyl-terminated liquid nitrile rubber; the raw materials for forming the adhesive layer in Comparative Example 1 include trichloroisocyanuric acid and polymethylene polyphenyl isocyanate, but do not include carboxyl-terminated liquid nitrile rubber.

[0039] In the infrared spectrum, 1280 cm -1 The infrared absorption peak at 1730 cm is the bending vibration peak of -NH in the urethane group. -1The absorption peaks at are mainly the stretching vibration peaks of -C=O. The signals of these two infrared absorption peaks are enhanced with the increase of the addition amount of terminal carboxyl liquid nitrile rubber, indicating that the addition of terminal carboxyl liquid nitrile rubber will continuously promote the reaction of -COOH in the terminal carboxyl liquid nitrile rubber and -NCO in the cast polyurethane, and finally obtain an urethane bond similar to the cast polyurethane material, which is characterized by having both -C=O and -NH chemical structures.

[0040] 2280 cm -1 The infrared absorption peak near the end mainly comes from the asymmetric vibration in -NCO. The signal of this absorption peak gradually weakens with the increase of the amount of carboxyl-terminated liquid nitrile rubber added, but when the amount of carboxyl-terminated liquid nitrile rubber added reaches 20wt%, the signal of this absorption peak rebounds. Therefore, it can be inferred that the increase in the amount of carboxyl-terminated liquid nitrile rubber added is conducive to the reaction of -COOH in the carboxyl-terminated liquid nitrile rubber and -NCO in the vulcanized rubber, and continuously consumes the -NCO group, but when the amount of carboxyl-terminated liquid nitrile rubber added reaches 20wt%, due to the influence of the "shielding effect", it will be unfavorable for the reaction, so compared with the case where the amount of carboxyl-terminated liquid nitrile rubber added is 15wt%, the absorption peak signal rebounds.

[0041] 2850-3070cm -1 Most of them are CH bending absorption peaks in alkane groups. The absorption peak signals in this area show a trend of gradual strengthening with the increase of the addition amount of terminal carboxyl liquid nitrile rubber.

[0042] (2) Determination of bonding properties With reference to the standard "GBT2790-1995 Adhesive 180 degree peel strength test method for flexible material bonding", the composite materials obtained in the examples and comparative examples were prepared into bonding specimens of standard size, and peel tests (normal temperature peel test and 80°C environmental chamber peel test) were carried out to evaluate the bonding strength between the vulcanized rubber and the cast polyurethane in the composite materials.

[0043] The sample preparation process in this embodiment and the comparative example is different from the above-mentioned reference standard in that, before surface treatment, tetrafluoroethylene tape (width 7.5 mm) is used to cover the two sides of the sample strip on both sides of the vulcanized rubber, so as to limit the width of the surface treatment area of ​​the vulcanized rubber to within 10 mm (except for comparative example 5, the tape needs to be removed before pouring for the other samples). The main purpose of this is to reduce the bonding area of ​​the bonding surface, while ensuring that the flexible material on both sides of the bonding surface is wide enough and the substrate strength is large enough, so that no premature breakage occurs before completing the room temperature T-type peel test, so as to obtain a more accurate T-type bonding strength value (the maximum bonding strength can be obtained when the maximum force ratio is ≥10).

[0044] The test results are shown in Table 1 and Table 2.

[0045] Table 1 Peel test results of Examples 1-5

[0046] Table 2 Peel test results of comparative examples 1-5

[0047] Comparing Comparative Example 3 with Comparative Example 5, it can be seen that after the vulcanized rubber surface is treated with 3wt% trichloroisocyanuric acid-acetone solution, the T-type bonding strength is improved, indicating that the vulcanized rubber surface has improved affinity for cast polyurethane under the dual effects of oxidation and halogenation.

[0048] Comparing Comparative Example 1 with Comparative Example 3, it can be seen that after the introduction of polymethylene polyisocyanate, the T-type bonding strength is significantly improved from 6.8 kN / m to 15.7 kN / m. It can be considered that the -NCO group with higher reactivity inside the polymethylene polyisocyanate plays a role in connecting the cast polyurethane and the oxygen-containing groups of the surface-treated vulcanized rubber.

[0049] By comparing Example 1 with Comparative Example 1, it can be seen that after further introducing the carboxyl-terminated liquid nitrile rubber, the T-type bonding strength is further improved.

[0050] See Example 1-5. As the proportion of the terminal carboxyl liquid nitrile rubber in the two-component adhesive used increases, the T-type bonding strength shows a trend of first increasing and then decreasing. It is speculated that as the proportion of the terminal carboxyl liquid nitrile rubber in the two-component adhesive used increases, the corresponding adhesive layer begins to undergo a cross-linking reaction in the pre-curing stage at 100°C, producing a chain segment of a certain molecular weight; and as the cast polyurethane is poured, the molecular chain of the adhesive layer is cured together with the molecular chain of the cast polyurethane through the urethane bond under the action of the chain extender, forming a certain amount of molecular chain entanglement, thereby improving the bonding effect, and due to the presence of butadiene structural units in the terminal carboxyl liquid nitrile rubber, it has a strong affinity with the rubber surface, which is conducive to the diffusion of the adhesive layer on the rubber side, so after curing, a strong anchoring effect is formed, which improves the bonding strength between the adhesive layer and the rubber. When the amount of carboxyl-terminated liquid nitrile rubber added reaches 20wt%, combined with infrared spectrum analysis, it can be seen that the reaction between -NCO group and -COOH is inhibited at this time, and part of the carboxyl-terminated liquid nitrile rubber on the surface of the vulcanized rubber is only in a mechanically mixed state, without the formation of chemical bonds, and then agglomeration occurs in the adhesive layer, thereby forming a stress defect area. Therefore, when the amount of carboxyl-terminated liquid nitrile rubber added reaches 20wt%, the T-type bonding strength begins to decrease. When the amount of carboxyl-terminated liquid nitrile rubber added reaches 30wt%, the T-type bonding strength decreases significantly, further confirming the previous inference.

[0051] Comparing Example 1 with Comparative Example 2, since the rubber segments and terminal carboxyl groups on the carboxyl-terminated liquid nitrile rubber can still react with cast polyurethane and vulcanized rubber, the T-type bonding strength reaches 9 kN / m at room temperature, but is greatly attenuated to 4.87 kN / m at 80°C, indicating that the temperature resistance of this chemical connection is very unsatisfactory.

[0052] The T-peel strength of Comparative Example 4 is similar to that of Comparative Example 5, indicating that surface treatment of the vulcanized rubber by coating a surface treatment agent containing trichloroisocyanuric acid is very important for the bonding of the vulcanized rubber and the cast polyurethane.

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A vulcanized rubber-cast polyurethane composite material, characterized in that: The vulcanized rubber-casting polyurethane composite material is obtained by bonding and curing the surface-treated vulcanized rubber and the casting raw material through a two-component adhesive, and the casting raw material is a mixture of a prepolymer of the casting polyurethane and a chain extender; The surface treated vulcanized rubber is obtained by coating the surface of the vulcanized rubber with a surface treatment agent, wherein the surface treatment agent includes trichloroisocyanuric acid; The two-component adhesive comprises component A and component B, wherein component A comprises polymethylene polyisocyanate, and component B comprises liquid nitrile rubber, wherein the liquid nitrile rubber is at least one of carboxyl-terminated liquid nitrile rubber and hydroxyl-terminated liquid nitrile rubber; The mass ratio of the polymethylene polyisocyanate to the liquid nitrile rubber is 100:(5-20).

2. The vulcanized rubber-cast polyurethane composite material according to claim 1, characterized in that: The liquid nitrile rubber is the carboxyl-terminated liquid nitrile rubber, and the mass ratio of the polymethylene polyisocyanate to the carboxyl-terminated liquid nitrile rubber is 100:

15.

3. The vulcanized rubber-cast polyurethane composite material according to claim 1, characterized in that: The component A further comprises an organic solvent, and the component B further comprises a nano-oxide filler.

4. The vulcanized rubber-cast polyurethane composite material according to claim 3, characterized in that: The organic solvent includes at least one of chlorobenzene, acetone and ethyl acetate.

5. The vulcanized rubber-cast polyurethane composite material according to claim 3, characterized in that: The nano oxide filler includes at least one of nano zinc oxide and hydrophobic nano silicon dioxide.

6. The vulcanized rubber-cast polyurethane composite material according to claim 5, characterized in that: The mass ratio of the liquid nitrile rubber to the nano oxide filler is 100:1.

5.

7. The vulcanized rubber-cast polyurethane composite material according to claim 1, characterized in that: The chain extender includes at least one of diol, diamine and triamine, and the mass ratio of the chain extender to the prepolymer is (1-20):

100.

8. A method for preparing the vulcanized rubber-cast polyurethane composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The two-component adhesive is applied to the surface of the surface-treated vulcanized rubber, placed under ventilation at room temperature for 1 h-4 h, and then pre-cured at 100° C.-130° C. for 1 h-3 h to obtain the vulcanized rubber to be bonded; The vulcanized rubber-casting polyurethane composite material is obtained by pouring and curing; the pouring process includes the following steps: pouring the pouring raw material onto the surface of the vulcanized rubber to be bonded.

9. The method for preparing the vulcanized rubber-cast polyurethane composite material according to claim 8, characterized in that: The pouring treatment comprises the following process: adding the pouring material into a mold containing the vulcanized rubber to be bonded, so that the pouring material is poured onto the surface of the vulcanized rubber to be bonded.

10. The method for preparing the vulcanized rubber-cast polyurethane composite material according to claim 8, characterized in that: The curing temperature is 90° C.-110° C., and the curing time is at least 18 hours.

Citation Information

Patent Citations

  • Cross-linked hydrogenated butyronitrile type polyurethane

    CN106478924A

  • Vibrating diaphragm and sound production device

    CN114827870A

  • Surface treatment process of vulcanized rubber and application thereof

    CN116535716A

  • Modified nano-silica and preparation method thereof, and polyurethane elastomer and preparation method thereof

    CN117089035A

  • Method for retreading old tyre by using polyurethane elastomer material

    CN1460591A

Cited By

  • Composite solid wheel and preparation method thereof

    CN120156140A